The spark in the engine: creative workers in a global economy. (1st January 2007) - Ursula Huws,
Abstract : Introducing this volume, this paper summarises the contents and offers an analysis of the place of creative work in a global economy, focusing in particular on the restructuring of global value chains and the commodification of knowledge in a process which simultaneously opens up the possibility for new creative tasks for some workers whilst deskilling others. It concludes with a discussion of the contradictions that this presents for creative workers who may be offered a choice between disappointing their own creative aspirations or collaborating in their own exploitation.